Nationalism and the Challenge of Globalization for the Young Generation in Aceh and Riau - Fuadi Fuadi; Anwar Anwar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
In the present, the younger generation is far from the heroic span of '45 (the value of nationalism or the value of the spirit of our patriot nationality in 1945), it leds us to the problem of waning the spirit of nationalism and patriotism among the younger generation. In Aceh, the influence of prolonged conflict has an influence on the views of groups society in Aceh towards the existence of Indonesian country. It can be seen from discourse on secession (Aceh) from Indonesia country. Besides that, there are various actions show resistance to the Pancasila. On the other hand, in Riau, although there is no history of conflict like in Aceh, but an issue about  'Riau Independence' is already spreaded. Hence, in this study, a description of youth's nationalism spirit in Aceh and Riau will be presented, and it offers several solutions to reconstruct youth's nationalism spirit in Aceh and Riau